Constitutional protection of fundamental labour rights in Venezuela (Gestión y Gerencia, 2021)
The objective of this essay is to analyze the constitutional protection of fundamental labor rights from the Venezuelan constitutional positive law, contrasting it not only with works written by Venezuelan authors but also with the approach carried out by European authors. The research approach was qualitative and hermeneutics and comparative law were used as methods of analysis of the constitutional and theoretical texts in terms of fundamental labor rights. The main result shows the existence of local tools to achieve the effectiveness of the constitutional guarantees in Venezuela that protect the enjoyment of fundamental labor rights. In the same way, the existence of international tools for their protection was verified, as well as the receipt of this guarantee protection within domestic law, therefore it is concluded that there are mechanisms for the enforceability of fundamental labor rights, which does not always imply real protection for them.
Keywords: Amparo; constitution; demand; fundamental rights; guarantee